Design of Campus Activity Feedback Information System Based on Content Management System (CMS) - Muhtarom Muhtarom; Iqbal Mansis; Meri Mayang Sari; Ari Asmawati; Kristina Vaher (ADI Publisher, 2026)
The management of student activity evaluation often faces significant efficiency challenges due to feedback collection methods that are still manual, fragmented, and not well integrated, resulting in slow data recapitulation, high potential for data inconsistency, and difficulties in tracing historical evaluation archives, which ultimately weakens the effectiveness of decision-making in quality assurance processes. To address these issues, this study aims to design and develop a feedback information system based on the WordPress Content Management System (CMS), chosen for its flexibility, ease of implementation, extensibility, and capability to centralize data management without requiring complex technical infrastructure. The system development adopts the Waterfall model, consisting of systematic stages including requirements analysis, system design, implementation, and testing, ensuring that the development process is structured and measurable. The analysis stage identifies user needs and system requirements through observation and document review, while the design stage focuses on developing a user-friendly interface, structured data storage, and role-based access control for administrators and users. During implementation, WordPress is configured and customized through plugins and online feedback forms that enable automatic data processing and centralized archiving. Functional testing simulations demonstrate that the system operates according to its specifications and is capable of supporting online data input, automatic report generation, and efficient data management. Preliminary evaluation results indicate that the proposed system can reduce data recapitulation time by up to 70% compared to conventional methods, making it a practical solution for supporting the digitalization of quality assurance in student activity management.